Enhancing Peer Greeting Skills in Early Childhood Children with ASD Through SST - Shafa, Qisthy Fathiya; Susetyo, Budi (Angstrom Centre of Education, 2024)
This study investigates the efficacy of Social Skill Training (SST) in enhancing the social skills of children with autism spectrum disorder (ASD) during kindergarten years. Children with ASD often struggle with social interactions, hindering their integration into preschool environments. Using a quantitative approach with a Single Subject Research (SSR) A-B-A design, this research focused on improving the